Aesthetic Communication of 'Wiraga Alus Wirasa Tumus': A Semiotic Analysis of Waranggana Representation in the Wara Genjong Dance YouTube Video - Bagus Aditya Susanto; Tito Edy Priandono; Alwan Husni Ramdani (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2026)
The digitalization of the Wara Genjong dance on YouTube represents a critical transition of local Javanese traditions into global participatory culture. This study aims to analyze the aesthetic communication and digital representation of the waranggana within this virtual space. Employing a qualitative desk research approach, this study applies Roland Barthes' semiotic analysis to decode verbal and visual signs in the high-definition YouTube broadcast of the